2020
DOI: 10.7717/peerj.9474
|View full text |Cite
|
Sign up to set email alerts
|

Impact of homocysteine levels on clinical outcome in patients with acute ischemic stroke receiving intravenous thrombolysis therapy

Abstract: Background The purpose of this study was to retrospectively assess the potential correlation between clinical outcomes and homocysteine (Hcy) levels in acute ischemic stroke (AIS) patients after recombinant tissue plasminogen activator (rtPA) treatment. Methods AIS patients treated by rtPA were enrolled between September 2018 and March 2019 in the Stroke Center (Department of Neurology and Neurosurgery)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…(4) Hcy may serve as an independent risk factor influencing the survival outcome of AIS patients, particularly in Caucasians and Asians. Furthermore, our findings highlight that the Hcy level is a prognostic factor for AIS and suggest that thrombolytic therapy may be helpful in the high-risk subgroup of patients (Yao et al, 2016;Li L. et al, 2020).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…(4) Hcy may serve as an independent risk factor influencing the survival outcome of AIS patients, particularly in Caucasians and Asians. Furthermore, our findings highlight that the Hcy level is a prognostic factor for AIS and suggest that thrombolytic therapy may be helpful in the high-risk subgroup of patients (Yao et al, 2016;Li L. et al, 2020).…”
Section: Discussionmentioning
confidence: 58%
“…The initial search identified 236 articles. Eventually, 17 articles published from 2001 to 2020 were included (Fallon et al, 2001;Sacco et al, 2004;Mizrahi et al, 2005;Perini et al, 2005;Yoldas et al, 2007;Okubadejo et al, 2008;Tu et al, 2013;Unal et al, 2013;Kwon et al, 2014;Shi et al, 2015;Forti et al, 2016;Tang et al, 2016;Yao et al, 2016;Markaki et al, 2017;Zhong et al, 2017;Alfieri et al, 2020;Li L. et al, 2020) (Figure 1). All studies reported follow-up time.…”
Section: Eligible Studies and Quality Assessmentmentioning
confidence: 99%
“…e NHISS score is a scale for evaluating the neurological functional recovery status of patients with stroke. A high NHISS score indicates how serious the nerve damage is, indicating that the recanalization rate after thrombolysis is low for patients [22]. erefore, close observation of NHISS score changes in ICS patients with atrial fibrillation and early intervention in patients with high risk factors can help doctors effectively judge the severity of patients' disease and the outcome of curative effects and improve the effectiveness of clinical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, some publications showed no significant prognostic effect of tHcy on neurological deficits. For example, it was concluded that the clinical contribution of tHcy to the functional IS outcome in the first 3 months was negligible, despite the reliable association of these indicators [ 13 ]. In spite of the correlation of tHcy with the neurological deficit at admission, no association with the functional outcome was found after 3 and 6 months after IS [ 7 ].…”
Section: Introductionmentioning
confidence: 99%